2017
DOI: 10.1136/bmjopen-2016-014167
|View full text |Cite
|
Sign up to set email alerts
|

Improving swallowing outcomes in patients with head and neck cancer using a theory-based pretreatment swallowing intervention package: protocol for a randomised feasibility study

Abstract: IntroductionThe incidence of head and neck cancer (HNC) in the UK is rising, with an average of 31 people diagnosed daily. Patients affected by HNC suffer significant short-term and long-term post-treatment morbidity as a result of dysphagia, which affects daily functioning and quality of life (QOL). Pretreatment swallowing exercises may provide additional benefit over standard rehabilitation in managing dysphagia after primary HNC treatments, but uncertainty about their effectiveness persists. This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…23 Nilsen et al found that HNC survivors who were more than 6 years from treatment completion, reported an increase in swallowing dysfunction. 40,52,53 Preventive as well as curative swallowing therapy programs, both during and after radiotherapy, have been shown to result in better swallowing function. Studies assessing the impact of late dysphagia on QOL remain, however, scarce; novel prospective trials in this area still need to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Nilsen et al found that HNC survivors who were more than 6 years from treatment completion, reported an increase in swallowing dysfunction. 40,52,53 Preventive as well as curative swallowing therapy programs, both during and after radiotherapy, have been shown to result in better swallowing function. Studies assessing the impact of late dysphagia on QOL remain, however, scarce; novel prospective trials in this area still need to be undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is known that the consequences of dysphagia, for example, malnutrition, dehydration, and aspiration pneumonia, have a negative impact on daily functioning and QOL and can be life-threatening. 40,52,53 Preventive as well as curative swallowing therapy programs, both during and after radiotherapy, have been shown to result in better swallowing function. 50,51,[54][55][56][57] We, therefore, initiated two prospective trials, one investigating the effect of tongue strengthening exercises on long-term dysphagia in patients with HNC (ISRCTN14447678), the other assessing the effect of three different prophylactic swallowing programs on post-treatment swallowing function as well as determining the adherence to these programs in patients undergoing primary CRT for oropharyngeal squamous cell carcinoma (ISRCTN98243550).…”
Section: Discussionmentioning
confidence: 99%
“…A full protocol of this study has been published (12). In summary, this was a two-arm parallel group non-blinded randomised controlled feasibility trial allocated in a 1:1 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Fifty to 60% of the HNC patients undergoing CRT may experience significant post-treatment dysphagia involving both muscle weakness and incoordination/timing issues [6][7][8]. The medical consequences (e.g., feeding-tube dependency, malnutrition, aspiration pneumonia) have a major negative impact on daily functioning and health-related quality of life (QOL) and can even be life-threatening [9][10][11][12][13][14][15]. These consequences and the high prevalence of swallowing disorders in HNC patients stress the importance of prevention, monitoring and management of this problem [16].…”
Section: Introductionmentioning
confidence: 99%